2022
DOI: 10.1111/joa.13737
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and function of the fused anuran radioulna

Abstract: Many clades of vertebrates exhibit fusion between elements of the appendicular skeleton. Well-known examples are found in the limbs of modern birds and mammals. These include the tibiotarsus, tarsometatarsus, and carpometacarpus bones in birds, the fused radius and ulna in bats, horses, and artiodactyls (Figure 1d), and the fused tibia and fibula in hedgehogs, sea-lions, coneys, rodents, rabbits, armadillos, aardvarks, and tarsiers (Barnett & Napier, 1953;Sahd et al., 2019;Salami et al., 2011). In extant frogs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…fusion and loss of carpal and tarsal bones and alteration of the phalangeal formula; Cooper et al, 2007 ; Hamrick, 2001 ; Holder, 1983 ; Luo et al, 2015 ; Saxena et al, 2017 ). Except for lineages that have undergone complete limb loss such as snakes and caecilians, the meristic composition of proximal segments is much more conserved than that of the autopod, displaying some but less frequent cases of element reduction and partial fusion of the zeugopod bones (observed in anurans, bats, manatees, horses, etc., Holder, 1983 ; Keeffe and Blackburn, 2022 ; Sears et al, 2007 ). Although this meristic information is useful to quantify major evolutionary changes in element composition, most of the morphological variation observed in the limbs results from changes in the shape and relative size of individual elements (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…fusion and loss of carpal and tarsal bones and alteration of the phalangeal formula; Cooper et al, 2007 ; Hamrick, 2001 ; Holder, 1983 ; Luo et al, 2015 ; Saxena et al, 2017 ). Except for lineages that have undergone complete limb loss such as snakes and caecilians, the meristic composition of proximal segments is much more conserved than that of the autopod, displaying some but less frequent cases of element reduction and partial fusion of the zeugopod bones (observed in anurans, bats, manatees, horses, etc., Holder, 1983 ; Keeffe and Blackburn, 2022 ; Sears et al, 2007 ). Although this meristic information is useful to quantify major evolutionary changes in element composition, most of the morphological variation observed in the limbs results from changes in the shape and relative size of individual elements (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The history of anuran morphometrics is dominated by a focus on the relationship between limb lengths and jumping performance (Rand, 1952 ; Zug, 1972 ; Dobrowolska, 1973 ; Choi et al, 2003 ; James et al, 2005 ; James et al, 2007 ; James & Wilson, 2008 ; Herrel et al, 2016 ). In contrast, other types of locomotor modes, including walking, hopping, swimming, burrowing and climbing, have received comparatively less attention (Emerson, 1979 ; Wells, 2007 ; Robovska‐Havelkova et al, 2014 ; Vassallo et al, 2021 ), as have regions of the body other than the pelvis and hindlimb such as the forelimb, hands and feet (Manzano et al, 2008 , 2019 ; Keeffe & Blackburn, 2020 , 2022 ; Abdala et al, 2022 ). Despite their relatively conserved body plan (Lires et al, 2016 ), extant anurans show considerable modifications in their skeletal proportions, reflecting their ability to respond to various mechanical challenges and inhabit diverse environments (Citadini et al, 2018 ; Gomes et al, 2009 ; Moen, 2019 ; Moen et al, 2013 ; Simons, 2008 ; Soliz et al, 2017 ; Vidal‐García et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…FEA involves dividing the object into polygonal elements and assigning material properties to the object to model its physical behaviour ( Richmond et al, 2005 ; Rayfield, 2007 ; Bright, 2014 ; Blasi-Toccacceli et al, 2022 ). Keeffe and Blackburn (2022) used FEA to investigate the mechanical implications of radioulnar fusion in frogs, concluding that the semi-fused condition present in frogs is associated with smaller von Mises stress and higher bending resistance than in unfused or completely fused conditions. FEA of the carpal bones of a chimpanzee revealed that scaphoid–centrale fusion has lower stresses in knuckle walking than lack of fusion, supporting this fusion's role in that behaviour and its evolution ( Püschel et al, 2020 ).…”
Section: Spectrum Of Digital Modelling Methods: Toward Theoretical Ap...mentioning
confidence: 99%